Factors Affecting Nurse Retention in A Private Healthcare System in Malaysia - Zarin Ikmal Zan Mohd Zain; Annamma Kunjukunju; Goventhamma Subramaniam; Nur Izzana Tajuddin (Jurnal Keperawatan Indonesia)
Nurse retention has become increasingly challenging in the post-pandemic era, particularly for private hospitals. This study aimed to identify the significant predictors of nurse retention in selected private hospitals in Malaysia. A quantitative, descriptive, cross-sectional design was employed. A pre-validated, self-administered questionnaire, distributed via Google Forms, was used for data collection. The respondents included 532 registered nurses employed at three private hospitals in Malaysia. Data analysis was conducted using descriptive statistics and correlation studies, including Spearman’s rho and multiple regression analysis. Among the participants, 54% reported good job satisfaction, 27.37% expressed organizational commitment, 25.97% were satisfied with human resource practices, and 48.41% intended to remain with their current organization. The findings revealed a strong positive correlation between nurse retention, organizational commitment, human resource practices, and job satisfaction. Multiple regression analysis indicated that job satisfaction was the most significant predictor of nurse retention (F (1) = 285.334, p (.000) < .05, R2 = 0.354), followed by human resource practices and organizational commitment. These results suggest that job satisfaction is the primary factor influencing nurse retention in private healthcare settings. Therefore, hospitals must implement strategies to enhance employees’ job satisfaction. Human resource management must also establish clear policies on remuneration, career development, and employee promotion to improve nurse retention.